2008
DOI: 10.1007/s00441-008-0735-0
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte apoptosis enhanced at the growth plate: a physeal response to a diaphyseal fracture

Abstract: Post-traumatic overgrowth of growing long bones is a common clinical phenomenon in paediatric traumatology and is the result of an enhanced stimulation of the nearby growth plate after fracture. To date, the exact post-fractural reactions of the growth plate are poorly understood. The aim of this study has been to determine the impact of fracture on the frequency of chondrocyte apoptosis of the growth plate. Rats sustained a mid-diaphyseal closed fracture of the left tibia or were left untreated. All animals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
4
7
0
Order By: Relevance
“…Morphological analysis of our study supports literature data [2,4,6,7,14–18]. When the bone bridge is large enough, the defect will result in some growth arrest, leading to angular deformities or longitudinal shortening [8].…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Morphological analysis of our study supports literature data [2,4,6,7,14–18]. When the bone bridge is large enough, the defect will result in some growth arrest, leading to angular deformities or longitudinal shortening [8].…”
Section: Resultssupporting
confidence: 85%
“…These data were also strengthened by Western Blot analysis, in vitro , where caspase-3 and cleaved PARP-1 expression significantly increased in growth plate chondrocytes with a time-course progression in experimental rats. Although we used apoptotic markers, such as caspase-3 and cleaved PARP-1, different from those used by other researchers, our study supports data from literature [2,7]. In the current study, we also investigated the expression of IL-6 and TNF-α serum levels within 24 h after growth plate damage, coinciding with the initial acute transient inflammatory phase, which was accompanied by a large influx of immune cells to the injury site.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Our study found that chondrocyte apoptosis occurred during the entire period of fracture healing; this finding is consistent with previous findings (18). Chondrocyte apoptosis increased during the process of fracture healing, reaching a peak on day 20 post-fracture, at which point the proliferation of chondrocytes was in decline, Numerous typical hypertrophic chondrocytes were observed in cartilage tissue, suggesting that apoptosis enhanced the maturation of cartilage tissue and endochondral ossification (19). In the present study, no significant difference in chondrocyte apoptosis was noted between the sx and ovx rats.…”
Section: Discussionsupporting
confidence: 93%
“…In children, fractured long bones tend to overgrow with respect to their counterparts (Aitken et al, 1939;Wray and Goodman, 1961), and there is an increase in apoptosis in the growth plate (Gaber et al, 2009). Interestingly, both the healing site and growth plate tend to have a more negative potential compared with that of the nearby intact tissue (Friedenberg and Brighton, 1966;Black, 1986) (Fig.…”
Section: Electrical Implications Of Corrosion For Osseointegration Ofmentioning
confidence: 99%